1963
DOI: 10.1055/s-0037-1621206
|View full text |Cite
|
Sign up to set email alerts
|

Strahlenbelastung durch Hg203-markierte Testpräparate zur Nierendiagnostik

Abstract: ZusammenfassungIn die Isotopendiagnostik der Nierenerkrankungen sind neuerdings Hg203-markierte Testpräparate eingeführt worden. Die Berechnung der Strahlenbelastung durch Radiosalyrgan ergab an Hand charakteristischer Fälle eine mittlere Gonadendosis für den Mann von 0,018 und für die Frau von 0,060 rad bei Applikation von 100 μC Hg203. Für Neohydrin lagen die entsprechenden Werte bei 0,028 bzw. 0,075 rad. Ganzkörper- und Nierenbelastung wurden ebenfalls für beide Präparate bestimmt. Nach den vorliegenden Beo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1965
1965
1965
1965

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…have been extended during the last ten years by the eployment of two radioisotope methods, radiorenography and scanning. Schumacher ( 14) used 131 J-Urographin, Haynie et al (5) 131 J-Hippuran and Kloss (7) 203 Hg-Salyrgan in their scanning investigations. Borghraef et al (2) in their animal experiments found 203 Hg-labelled Neohydrin a suitable contrast material for kidney scanning.…”
mentioning
confidence: 99%
“…have been extended during the last ten years by the eployment of two radioisotope methods, radiorenography and scanning. Schumacher ( 14) used 131 J-Urographin, Haynie et al (5) 131 J-Hippuran and Kloss (7) 203 Hg-Salyrgan in their scanning investigations. Borghraef et al (2) in their animal experiments found 203 Hg-labelled Neohydrin a suitable contrast material for kidney scanning.…”
mentioning
confidence: 99%